Solar - McEwan, Ian (London : Vintage Books, 2011)
Ranging from the Arctic Circle to the deserts of New Mexico,'Solar' is a serious and darkly satirical novel, showing human frailty struggling with the most pressing and complex problem of our time. It is a story of one man's greed and self-deception.
Originally published: London: Jonathan Cape, 2010.
Keywords: Middle-aged men -- Fiction; Physicists -- Fiction; Nobel Prize winners -- Fiction; English fiction